High dose rates obtained outside ISS in June 2015 during SEP event. (June 2016) - Dachev, T.P.; Tomov, B.T.; Matviichuk, Yu.N.; Dimitrov, Pl.G.; Bankov, N.G.
Highlights: The Bulgarian build R3DR2 instrument on the European Space Agency (ESA) EXPOSE-R2 platform outside the Russian "Zvezda" module of the International Space Station (ISS) was described. The dosimetric characteristics of the solar energetic particles (SEP) event, observed on 22 June 2015 were analyzed. The main finding of the study is that SEP protons produced high dose rates outside ISS, reaching values >5000 µGy h −1 . SEPs similar to that observed on 22 June 2015 could be of the most dangers events for the cosmonauts/astronauts involved in extravehicular activity (EVA). Abstract: The R3DR2 instrument performed measurements in the European Space Agency (ESA) EXPOSE-R2 platform outside the Russian "Zvezda" module of the International Space Station (ISS) in the period 24 October 2014–11 January 2016. It is the Liulin-type deposited energy spectrometer (DES) (Dachev et al., 2015a). Took place in November 2014, this was the first attempt to monitor a small solar energetic particle (SEP) event outside ISS using the Liulin-type DES (Dachev et al., 2015d). In this study, we describe the dosimetric characteristics of the largest SEP event, observed on 22 June 2015 with the R3DR2 instrument outside ISS. The main finding of this study is that SEP protons with a minimum energy of approximately 7 MeV at the surface of the R3DR2 detector produced high dose rates, reaching >5000 µGy h −1, while the inner radiation belt maximum dose was at the level of 2200 µGy h −1 . If a virtual external vehicle activity (EVA) was performed in the same period of the SEP maximum on 22 June 2015, the doses obtained in the skin of cosmonauts/astronauts can reach 2.84 mGy after 6.5 h, which is similar to the average absorbed dose inside ISS for 15 days (Reitz et al., 2005). A comparison with other extreme events measured with Liulin-type instruments shows that SEPs similar to that observed on 22 June 2015 could be one of the most dangerous events for the cosmonauts/astronauts involved in EVA.